2015
DOI: 10.1017/s136898001500333x
|View full text |Cite
|
Sign up to set email alerts
|

Birth registration and child undernutrition in sub-Saharan Africa

Abstract: Objective: In many countries of the world millions of people are not registered at birth. However, in order to assess children's nutritional status it is necessary to have an exact knowledge of their age. In the present paper we discuss the effects of insufficient or imprecise age data on estimates of undernutrition prevalence. Design: Birth registration rates and levels of stunting, underweight and wasting were retrieved from Multiple Indicator Cluster Surveys and Demographic and Health Surveys of thirty-seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 20 publications
4
28
2
Order By: Relevance
“…In fact, we excluded 225 children (21.3%) from the total sample, due to their lack or incorrect dates of birth. Such exclusion represents an unintentional selection bias that likely caused the underestimation of undernutrition, according to the results of Comandini et al () and Jeong et al (). Indeed, children whose births are more accurate generally belong to the better‐educated and also better‐nourished segments of the population (Comandini et al, ).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…In fact, we excluded 225 children (21.3%) from the total sample, due to their lack or incorrect dates of birth. Such exclusion represents an unintentional selection bias that likely caused the underestimation of undernutrition, according to the results of Comandini et al () and Jeong et al (). Indeed, children whose births are more accurate generally belong to the better‐educated and also better‐nourished segments of the population (Comandini et al, ).…”
Section: Discussionmentioning
confidence: 96%
“…One of the methodological challenges faced during nutritional assessment in sub‐Saharan Africa is the insufficient and imprecise information on child age (Comandini, Cabras, & Marini, ; Comandini, Cabras, & Marini, ; Finaret & Hutchinson, ; Jeong, Bhatia, & Fink, ; Larsen, Headey, & Masters, ). In fact, without reliable information about a child's age, the indicators stunting, underweight, and obesity (defined in relation to sex and age), according to standard criteria (WHO, ) cannot be accurately calculated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…"In these regions, children without a certain date of birth-month and year-have zero probability of selection in large epidemiological studies on nutritional status", said anthropologist Elisabetta Marini from the University of Cagliari, Italy. "We have shown that in sub-Saharan Africa a selection bias favouring registered children is present in demographic and health surveys, and can lead to underrate undernutrition prevalence" [9]. Guessing the age of unregistered children by asking parents is prone to inaccuracies, often ending up with an undervaluation of the age of these children, especially if they are stunted.…”
Section: Embo Reportsmentioning
confidence: 97%